2015
DOI: 10.1590/s0036-46652015000100013
|View full text |Cite
|
Sign up to set email alerts
|

ELEVATED TRANS-MAMMARY TRANSMISSION OF Toxocara canis LARVAE IN BALB/c MICE

Abstract: Toxocariasis is a widespread zoonosis and is considered an important worldwide public health problem. The aim of this study was to investigate the frequency of trans-mammary Toxocara canis infection in newborn BALB/c mice nursed by females experimentally infected with 1,200 eggs after delivery. After 50 days of age, the presence of larvae in different organs of the offspring was investigated. Trans-mammary infection was confirmed in 73.9% of the mice that had been nursed by infected females. These data show a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…The importance of the transmammary route in the transmission of T. canis in mice was emphasized by a group of researchers from the Federal University of Rio Grande, in the state of Rio Grande do Sul. 115,116 The migration patterns of T. canis were studied in experimental infections of mice and gerbils. In Rattus norvegicus, a significant difference was found between the migration patterns according to the sex of the animals.…”
Section: Experimental Studies In Nonhuman Paratenic Hostsmentioning
confidence: 99%
“…The importance of the transmammary route in the transmission of T. canis in mice was emphasized by a group of researchers from the Federal University of Rio Grande, in the state of Rio Grande do Sul. 115,116 The migration patterns of T. canis were studied in experimental infections of mice and gerbils. In Rattus norvegicus, a significant difference was found between the migration patterns according to the sex of the animals.…”
Section: Experimental Studies In Nonhuman Paratenic Hostsmentioning
confidence: 99%
“…However, studies using experimental models have confirmed the transmission of Toxocara larvae via transmammary routes, by examining tissue samples of neonatal mice (REITEROVÁ et al, 2003;JIN et al, 2008;SOUZA AGUIAR et al, 2014), mice at 50 days of age (TELMO et al, 2015), and directly through rabbit milk (SANTARÉM et al, 2014). Nonetheless, the limit of detection of the technique presented by these authors in detecting larvae has not been evaluated.…”
Section: Transmission Of T Canis In Dogs Is Predominantlymentioning
confidence: 99%
“…Toxoplasmosis, which stands out as a major public health problem and a serious disorder during pregnancy, can cause abortion, fetal death, impaired fetal growth and congenital infection, with serious consequences to the neonate (Tenter et al , 2000; Pappas et al , 2009). Although vertical transmission of toxocariasis has been recorded only once (Maffrand et al , 2006), its importance in the transmission of Toxocara canis has been widely proven, as has the potential risk of complications it poses during pregnancy (abortion and impaired fetal growth), according to studies involving experimental models (Schoenardie et al , 2013a; Aguiar et al , 2015; Telmo et al , 2015). Moreover, the seroprevalence of Toxocara spp.…”
Section: Introductionmentioning
confidence: 99%